2021
DOI: 10.1093/geronb/gbab046
|View full text |Cite
|
Sign up to set email alerts
|

Are Older Adults More Optimistic? Evidence From China, Israel, and the United States

Abstract: Objectives Optimistic bias refers to the phenomenon that individuals believe bad things are less likely to happen to themselves than to others. However, whether optimistic bias could vary across age and culture is unknown. The present study aims to investigate: 1) whether individuals exhibit optimistic bias in the context of COVID-19 pandemic; 2) and whether age and culture would moderate such bias. Method 1051 participants r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This study showed that older age was associated with the tendency of an optimistic perception. A previous study reported that the association between age and optimistic bias against the risk of COVID-19 was stronger in China than in the US and Israel ( Lin et al, 2021 ). The authors attributed this difference to the cultural context and argued that optimistic bias could be reinforced with aging in a society with strong ties.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that older age was associated with the tendency of an optimistic perception. A previous study reported that the association between age and optimistic bias against the risk of COVID-19 was stronger in China than in the US and Israel ( Lin et al, 2021 ). The authors attributed this difference to the cultural context and argued that optimistic bias could be reinforced with aging in a society with strong ties.…”
Section: Discussionmentioning
confidence: 99%
“…A critical takeaway from the work in this special section is the finding that well-being among older adults during the COVID-19 pandemic likely varies greatly based on demographic characteristics, including age, gender, and race. A few of the papers in this collection consider these variables ( H. Lin et al, 2022 ; T. Lin et al, 2021 ; Pearman et al, 2021 ); however, more work is needed. Given that the COVID-19 pandemic has differentially affected subgroups of the population ( CDC, 2022 ), it is reasonable to expect that the processes associated with psychological vulnerability and/or resiliency also vary considerably based on demographic characteristics.…”
Section: Next Steps In Studying Psychological Aging and Covid-19mentioning
confidence: 99%
“… Lin et al (2022) evaluated loneliness progression among older adults in Florida (United States) and Ontario (Canada) at five time points during the first 6 months of the pandemic. They identified gender differences in the trajectory of loneliness between Florida and Ontario, with more loneliness among men in Florida and among women in Ontario.…”
mentioning
confidence: 99%
See 1 more Smart Citation